ChemInform Abstract: Magnetic Interactions in Molecules and Highly Correlated Materials: Physical Content, Analytical Derivation, and Rigorous Extraction of Magnetic Hamiltonians. Issue 8 (25th February 2014) - Malrieu, Jean Paul; Caballol, Rosa; Calzado, Carmen J.; de Graaf, Coen; Guihery, Nathalie
Abstract Review: 918 refs.